The e-Learning movement as a process of quality improvement in higher education - Nicolaou, Christiana T.; Constantinou, Constantinos P.; Nicolaidou, Iolie (My University, 2005)
Quality in education has been recognized as an issue that should guide our efforts for improvement of teaching and learning processes. e-learning is the latest attempt to take advantage of developments in technology to improve learning. In this paper, we discuss the possibility of establishing a theory of e-learning, the value of design patterns, and the possible scenarios of implementation by higher education institutions attempting to use new technologies. We present the results of a survey concerning students' and faculty members' views regarding e-learning implementation. Data collection was accomplished through a specially designed questionnaire administered to 1,938 students and 46 faculty members. Ten faculty members were also interviewed for more in-depth analysis. Based on the results of the survey, we propose a series of actions which could form the basis for developing an e-learning policy through continuous improvement of a university's teaching program and we discuss wider implications for teaching and learning.
Keywords: Ε-Learning; Ε-Learning movement; Quality improvement; Higher education